2018
DOI: 10.1111/mice.12351
|View full text |Cite
|
Sign up to set email alerts
|

Unified Vision‐Based Methodology for Simultaneous Concrete Defect Detection and Geolocalization

Abstract: Vision‐based autonomous inspection of concrete surface defects is crucial for efficient maintenance and rehabilitation of infrastructures and has become a research hot spot. However, most existing vision‐based inspection methods mainly focus on detecting one kind of defect in nearly uniform testing background where defects are relatively large and easily recognizable. But in the real‐world scenarios, multiple types of defects often occur simultaneously. And most of them occupy only small fractions of inspectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 69 publications
0
85
0
Order By: Relevance
“…They demonstrated that the SSD could obtain relatively high accuracy for some classes of defect. However, some researchers found that directly locating objects using such single‐stage detectors could compromise the accuracy of the detection (Li et al., ; L. Wang et al., ). In particular, the earliest version of YOLO could hardly detect objects with unusual aspect ratios or configurations (Redmon et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the SSD could obtain relatively high accuracy for some classes of defect. However, some researchers found that directly locating objects using such single‐stage detectors could compromise the accuracy of the detection (Li et al., ; L. Wang et al., ). In particular, the earliest version of YOLO could hardly detect objects with unusual aspect ratios or configurations (Redmon et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a more carefully configured deep neural network (DNN) is essential for solving the true variety of real‐world problems. For example, different DNNs have been proposed to identify cracks in images with disturbing background interference (F. C. Chen & Jahanshahi, ; Kang & Cha, ; R. Li, Yuan, Zhang, & Yuan, ; Liang, ; Y. Xu, Bao et al., ). In addition, the noising issues and the layer multiplexing scheme in DNNs have been discussed (Koziarski & Cyganek, ; Ortega‐Zamorano, Jerez, Gómez, & Franco, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, computer vision-based approaches have been studied (Koch, Georgieva, Kasireddy, Akinci, & Fieguth, 2015; © 2019 Computer-Aided Civil and Infrastructure Engineering Tizani & Mawdesley, 2011), and it has been shown that there is a need for automatic detection and techniques for classification of distresses that have occurred in road structures (O'Byrne, Schoefs, Ghosh, & Pakrashi, 2013;Zalama, Gómez, Medina, & Llamas, 2014). Because various kinds of distress occur in road structures (Li, Yuan, Zhang, & Yuan, 2018;H. Maeda, Sekimoto, Seto, Kashiyama, & Omata, 2018), the goal of our work is the realization of an accurate distress classification method based on machine learning techniques using images taken of distress parts of road structures.…”
Section: Introductionmentioning
confidence: 99%